Health promoting schools in Kerala, India - Heljo Padamadan Joseph; Ramanarayanan Venkitachalam; Joe Joseph; Chandrashekar Janakiram (Wolters Kluwer Medknow Publications, 2019)
Introduction: Health promoting school (HPS) is a holistic concept where health and learning coexist. The objective of this study was to assess the health promoting standards of schools in Kerala. Methodology: A cross-sectional study was designed in Kerala, India, with schools in Kerala as a study unit. A questionnaire which consisted of 37 items across eight domains of the HPS concept was developed and validated. The schools were then graded into compliant and not compliant categories based on scores obtained. Bivariate and multivariate analysis was also done. Results: Of 120 schools, 90.8% were compliant toward health education domain and only 8.3% were compliant with nutrition services. Majority of schools showed compliance with the other six domains. Average overall scores were 153 (58.8%) with the equal number of schools in both compliant and not compliant categories. There was a significant association between health education and physical education domain with respect to the type of school, i.e., privately managed had six times more chances of being compliant toward health education domain compared to government schools (odds ratio [OR] 6.05; 95% confidence interval [CI] 1.10-33.29). Hence, also private schools had two times more chance of being compliant toward physical education compared to government schools (OR 2.52; 95% CI 1.0 - 4.32). Physical education domain showed a significant association with respect to geographic region, i.e., the schools in North Kerala were found to be three times more compliant compared to South Kerala (OR 3.48; 95% CI 1.05-11.53). Conclusions: Despite the good health and social indicators in Kerala, there is a deficiency in schools promoting health of children. A coordinated effort by the government and the education system can convert existing schools into health promoting.